The archaeological implications of water-cached hyena kills - Selvaggio, M.M. (Current Anthropology, 1998)
Keywords: dept.ant

Concerning the three stage model of carcass processing at FLKZinjanthropus: A reply to Capaldo - Selvaggio, Marie M (Journal of Human Evolution, 1998)
Keywords: Animals; Anthropology; Carnivora; Feeding Behavior; Fossils; Hominidae; Humans; Models, Biological; animal; anthropology; biological model; dept.ant; feeding behavior; fossil; hominid; human; note; peer-reviewed; ⛔ No DOI found

Evidence for a three-stage sequence of hominid and carnivore involvement with long bones at FLKZinjanthropus, olduvai gorge, tanzania - Selvaggio, Marie M (Journal of Archaeological Science, 1998)
The order in which hominids and carnivores had access to Plio-Pleistocene bone assemblages has defied interpretation despite attempts to decipher their sequence from element frequencies or by comparing ancient butchery marks with modern ones. Data from two simulations in which experimental stone-tool butchery of long bones occurred after carcasses were defleshed by large free-ranging East African carnivores are here compared to data from the FLK Zinjanthropus bone assemblage from Olduvai Gorge, Tanzania. One experimental sample simulated two stages of tissue removal; defleshing of long bones by carnivores, followed by tool-assisted flesh-scrap removal and marrow extraction. A second simulated three stages of tissue removal; the first two stages the same as the first sample, plus a third stage in which bone-crunching carnivores ravaged the remains. Carnivore ravaging is demonstrated to result in additional tooth marks on epiphyseal fragments, but does not significantly alter the incidence of defleshing tooth marks or butchery marks on midshafts. The Zinjanthropus sample is similar to the three-stage simulation in its proportion of epiphyseal relative to midshaft fragments, and for the incidence of midshafts bearing tooth marks and butchery marks. © 1998 Academic Press Limited.
Keywords: Butchery Marks; Carnivore Tooth Marks; Experimental Archaeology; Pleistocene; Pliocene; Scavenging; Site Formation; Tanzania; Taphonomy; archaeology; bone assemblage; dept.ant; taphonomy